The Postmodernism Revolution In The Art World Of Lady Gaga - Pratomo, Evan Raditya (Universitas Ciputra, 2019)
The art world changes from time to time. Likewise, in the world of singing, this has turned to postmodern. In the field of music industry, it is also shifting to postmodern culture, which is marked by the rise of the interests of popular culture as part of commodity culture and the culture of consumerism, capitalism. The phenomenon of the artist Lady Gaga always attracts public attention. Style, appearance, video clips and choreographers often cause controversy Cultural changes can be seen starting from video clips, choreographers in each stage, appearance, manner of dress, make-up show the characteristics of postmodernism.